The Impact Of Accounting Information System, Human Resources And The Use Of Siskeudes On The Quality Of Financial Reports In Villages In Sambi District - Fita Nurna Sari; Winda Septiani; Putri Novitasari; Nur Asih Triatmaja; Unna Ria Safitri (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The performance of the village government can be reflected through the financial statements prepared. Financial reports can be one of the accurate evidence in channeling the right budget to improve community welfare. This study aims to determine how internal control, accounting information systems, the quality of human resources, and the use of SISKEUDES on the quality of financial statements in all villages of Sambi District. Data collection was done through purposive sampling method by distributing 62 questionnaires. Through the research, it was found that the internal control system and SISKEUDES had a negative and insignificant impact on the quality of financial statements. In contrast, the accounting information system and the quality of human resources have a positive and insignificant impact on the quality of financial statements.